2007
DOI: 10.1021/nl0707914
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Self-Aligned p-Type In2O3 Nanowire Arrays Epitaxially Grown on Si Substrates

Abstract: Lateral orientated growth of In 2 O 3 nanowire (NW) and nanorod (NR) arrays has been achieved by a vapor transport and condensation method on (001) and (111) surfaces of Si substrates. The single crystalline In 2 O 3 NWs and NRs were grown along [21 h1 h] in parallel to the Si ±[11 h0] and lying in the substrate plane. The electrical measurements show that the In 2 O 3 NWs are p-type semiconductor. By N + doping, the resistivity of the In 2 O 3 NWs has been tuned. The lateral self-aligned In 2 O 3 NW and NR ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…It has been demonstrated that a decrease in size of the In 2 O 3 crystallites in the sensing layer can considerably enhance the response [38]. Thus, there have been a large number of researches on the synthesis and characterization of nanostructured In 2 O 3 [39]. The enhancement of the gas-sensing characteristics by the formation of nanocomposites, such as In 2 O 3 -ZnO, In 2 O 3 -SnO 2 , and In 2 O 3 -CeO 2 [38,40,41] was also explored.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a decrease in size of the In 2 O 3 crystallites in the sensing layer can considerably enhance the response [38]. Thus, there have been a large number of researches on the synthesis and characterization of nanostructured In 2 O 3 [39]. The enhancement of the gas-sensing characteristics by the formation of nanocomposites, such as In 2 O 3 -ZnO, In 2 O 3 -SnO 2 , and In 2 O 3 -CeO 2 [38,40,41] was also explored.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional (1-D) metal-oxide nanostructures are currently the subject of much interest both for their novel structures and physical properties and for their potential applications in nanoelectronics and nanophotonics [1][2][3]. Many kinds of 1-D oxide, such as ZnO and SnO 2 , have been fabricated and studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although still challenging, procedures for achieving horizontal alignment of NWs are somewhat less restrictive since they are not limited to the direct growth of horizontally aligned NS [1,2] but can also be aligned using liquid suspensions of presynthesized NWs as well [3,4]. However, methods for obtaining vertically aligned semiconductor oxide NS require epitaxial growth, and in fact, vertically aligned NS of Ga 2 O 3 [5], InAs [6], In 2 O 3 [7,8], ZnGa 2 O 4 [9] and ZnO [10,11] have been successfully synthesized in this way. Currently, ZnO NWs have attracted a significant amount of attention due to the relative simplicity of their synthesis under a variety of conditions [12][13][14][15] and due to the wide array of potential applications (e.g., sensing [16], piezoelectricity [17] and field emission [18,19]).…”
Section: Introductionmentioning
confidence: 99%